Probiotics protect against RSV infection by modulating the microbiota-alveolar-macrophage axis - Ji Jian-jian; Sun Qin-mei; Nie Deng-yun; Wang Qian; Zhang Han; Qin Fen-fen; Wang Qi-sheng; Lu Sheng-feng; Pang Guo-ming; Lu Zhi-gang (Acta Pharmacologica Sinica, 2021)
Respiratory syncytial virus (RSV) is leading cause of respiratory tract infections in early childhood. Gut microbiota is closely related with the pulmonary antiviral immunity. Recent evidence shows that gut dysbiosis is involved in the pathogenesis of RSV infection. Therefore; pharmacological and therapeutic strategies aiming to readjust the gut dysbiosis are increasingly important for the treatment of RSV infection. In this study, we evaluated the therapeutic effects of a probiotic mixture on RSV-infected mice. This probiotic mixture consisted of Lactobacillus rhamnosus GG, Escherichia coli Nissle 1917 and VSL#3 was orally administered to neonatal mice on a daily basis either for 1 week in advance or for 3 days starting from the day of RSV infection. We showed that administration of the probiotics protected against RSV-induced lung pathology by suppressing RSV infection and exerting an antiviral response via alveolar macrophage (AM)-derived IFN-β. Furthermore, administration of the probiotics reversed gut dysbiosis and significantly increased the abundance of short-chain fatty acid (SCFA)-producing bacteria in RSV-infected mice, which consequently led to elevated serum SCFA levels. Moreover, administration of the probiotics restored lung microbiota in RSV- infected mice. We demonstrated that the increased production of IFN-β in AMs was attributed to the increased acetate in circulation and the levels of Corynebacterium and Lactobacillus in lungs. In conclusion, we reveal that probiotics protect against RSV infection in neonatal mice through a microbiota-AM axis, suggesting that the probiotics may be a promising candidate to prevent and treat RSV infection, and deserve more research and development in future.